A Brief History of Distance Education and Perspectives of its Future - Huszti , Ilona; Lekhner , Ilona; Baran , Adalbert (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
Relevance. Distance learning has undergone significant evolution since its inception in the mid-20th century, responding to technological progress, pedagogical innovations, and societal needs. Its relevance lies in providing flexible and accessible educational opportunities for students around the world. The purpose of the study is to trace the evolution of distance learning from its origins to the present, identify key factors that have influenced its development, and outline potential directions for its future development. The research objectives are to analyse the historical development of distance learning, identify key technological, pedagogical, and social factors that have influenced its evolution, determine the contribution of specialists and institutions to the development of distance learning, and outline potential directions for the development of distance learning in the future. Research results: 1. Key stages in the development of distance learning are identified, starting from training methods for military personnel in the 1940s to modern online platforms and MOOCs. 2. The impact of technological progress (personal computers, the Internet, Web 2.0) on expanding the capabilities and accessibility of distance learning is established. 3. The role of pedagogical innovations and changing societal needs in shaping modern models of distance learning is determined. 4. The current state of distance learning and its potential future directions are presented. Conclusions. Distance learning has gone from correspondence courses to interactive online platforms, significantly expanding access to education. Technological progress, pedagogical innovations, and changes in social needs are the driving forces of its evolution. Distance learning has significant potential for development and will become an integral part of the educational process of the future.